In Vitro Growth and Rooting of Mangosteen (Garcinia mangostana L.) on Medium with Different Concentrations of Plant Growth Regulator - FAUZIYAH HARAHAP; ROEDHY POERWANTO; . SUHARSONO; CICIK SURIANI; SUCI RAHAYU (Bogor Agricultural University, Indonesia, 2014)
Propagation of mangosteen is challenging for many reasons, including limited seed set, slow rate of seedling growth, and difficulty with root formations. The objective of this research was to find the best combination of medium and plant growth regulator for in vitro growth and rooting of mangosteeen seed. Various types of explant (a whole seed; seed divided into 2, 3, and 4 cross sections; seed divided into 2, 3, and 4 longitudinal sections) were treated with five concentrations of benzyl amino purine (BAP; 0, 2.5, 5, 7.5, 10 mg/L) for shoot induction in ½ Nitrogen (N) Murashige and Skoog (MS) medium. The shoots were rooted on MS and woody plant medium (WPM) media with several combinations of indole butyric acid (IBA) and naphtalene acetic acid (NAA). Treatments for root induction were applied as follows: (i) low dose, given during induction of rooting, (ii) soaking the base of the shoots in medium treated with a high dose of auxin for 5 days, and then growing the shoots in MS ½ N with 1 mg/L NAA + 1 mg/L BAP medium. Our result show that BAP positively affected mangosteen bud growth. The best medium for mangosteen shoot regeneration was found to be MS ½ N + 5 mg/L BAP. This medium induced the highest number of shoots from the seed explant cut into four cross sections. We found the best medium to induce in vitro rooting of mangosteen shoot was MS ½ N + 3 mg/L indole butiric acid (IBA) + 4 mg/L NAA medium. Some treatment negatively affected growth. Soaking the mangosteen shoot base in a medium with an overly high dose of auxin seemed to disrupt and inhibit growth of the mangosteen shoot.